TINJAUAN YURIDIS KEBERADAAN IZIN LOKASI UNTUK PEMBANGUNAN KEBUN KELAPA SAWIT DI KABUPATEN KUTAI BARAT DI TINJAU DARI PERATURAN MENTERI AGRARIA DAN TATA RUANG NOMOR 5 TAHUN 2015 TENTANG PEDOMAN IZIN LOKASI - Susilo, Kristian Heru (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACT One of the goals of industrial development in Indonesia is to increase company productivity and value added productivity. An increase in value added from a commodity that is achieved is through processing from raw to semi-finished and finished goods. In the process of land acquisition for oil palm plantation business, it must first pay attention to the status of available land, namely whether it is State Land, Land Rights or Land Management Rights. Then the Oil Palm Plantation Company that will acquire the land must also pay attention to the procedures for obtaining the land provided by the National Land Law, namely the project, its location and the available land status. It is expected that the government will be more strict in the supervision of oil palm plantations, so that there will be no land expansion that is done carelessly by plantation owners. Keywords: Location Permit, Oil Palm Plantation